2006
DOI: 10.1007/s10798-005-2109-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Teacher Knowledge and Authentic Formative Assessment on Student Learning in Technology Education

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 9 publications
1
21
0
2
Order By: Relevance
“…In related studies on the implementation of technology education in New Zealand, the important influence of PCK on technology teaching was affirmed (Jones and Compton 1998;Moreland and Jones 2000). The results of several other studies in primary technology education (Alamäki 1999;Fox-Turnbull 2006;Stein et al 2002) and primary science (Davis 2004;Smith 1999) are in line with this finding. Magnusson et al (1999) presented two important ideas about PCK.…”
Section: Pedagogical Content Knowledgesupporting
confidence: 60%
“…In related studies on the implementation of technology education in New Zealand, the important influence of PCK on technology teaching was affirmed (Jones and Compton 1998;Moreland and Jones 2000). The results of several other studies in primary technology education (Alamäki 1999;Fox-Turnbull 2006;Stein et al 2002) and primary science (Davis 2004;Smith 1999) are in line with this finding. Magnusson et al (1999) presented two important ideas about PCK.…”
Section: Pedagogical Content Knowledgesupporting
confidence: 60%
“…Results of multiple studies indicated that teachers need the ability to integrate AfL with pedagogical content knowledge (PCK) to be able to cater for their students' learning needs and provide useful feedback (Aschbacher & Alonzo, 2006;Birenbaum et al, 2011;Feldman & Capobianco, 2008;Fletcher & Shaw, 2012;Fox-Turnbull, 2006;Furtak, 2012 2,3,4,5,6,7,8,9,10,12,13,14,15,16,18,19,20,22,24,25 ,2,3,4,5,6,7,8,9,10,12,13,14,15,16,18,20,24,25 19 Teacher beliefs and attitudes 2,3,4,5,10,13,15,16,18,19,20,22 12 Assessment 1,2,…”
Section: Teacher Knowledge and Skillsmentioning
confidence: 99%
“…Other studies specifically found that 'discussion' is a pedagogy often used in AfL. Teachers should be able to foster the participation of students in discussions about their answers, expertise or feedback (Aschbacher & Alonzo, 2006;Bryant & Carless, 2010;Feldman & Capobianco, 2008;Fox-Turnbull, 2006;Gamlem & Smith, 2013;Gottheiner & Siegel, 2012;Hargreaves, 2013;Havnes, Smith, Dysthe, & Ludvigsen, 2012;Lee et al, 2012;Penuel et al, 2007). Discussion can give teachers valuable insight into students' thinking, difficulties and understanding.…”
Section: Teacher Knowledge and Skillsmentioning
confidence: 99%
“…However, assessment of students' ability to design and propose solutions goes far beyond the mere summative assessment of their knowledge and skills. The development of innovative teaching activities to meet the demands of ever more complex daily life situations for students, which often involves new materials, technologies and systems, can be very demanding for educators and curriculum developers (Fox-Turnbull, 2006, 2015Kimbell, 1997;Snape & FoxTurnbull, 2013 Given the sentiments above, Resnick (1987) points out the necessity in using the appropriate tools when solving tasks in school. She argues against a predominant view that "pure thought" activities are better than using tools such as computers or calculators arguing, "In contrast, most mental activities outside school are engaged intimately with tools, and the resultant cognitive activity is shaped by, and dependent upon, the kinds of tools available" (p. 13).…”
Section: Creating the Basis For Authentic Learning In Technology Educmentioning
confidence: 99%